Steganography in True Color Images Using Even Odd Bit Slicing (International Journal of Engineering and Computer Science, 2015)
Steganography is a tool for hiding information inside an image. It usually  deals  with  different approaches  of hiding  the  existence  of  the  communicated data or message in  a  way  that  it  remains  confidential.    It maintains integrity of message between two communicating bodies. In image steganography, message image is hidden in cover image and a stego-image is generated.  There are different types of steganography techniques having pros and cons. In  this  paper, we  review  the  various data hiding  techniques that  are  used  to  implement  a steganography such as LSB, ISB, MLSB etc.